Escapism and hyperreality in The Universal Baseball Association, Inc., J. Henry Waugh, Proprietor - Claudio Moreno, Esther (Estudios Ingleses de la Universidad Complutense, 2011)
In this article we intend to offer a sociological approach to Robert Coover’s The Universal Baseball Association, Inc., J. Henry Waugh, Proprietor based on Jean Baudrillard’s thinking. We consider Henry Waugh, the novel’s protagonist, the archtype of the baudrillardian postmodern subject and his Universal Baseball Association as a metaphorical representation of hyperreality. Given these premises, we will analyze the escape and encounter ways in a society inundated by media imagery and virtual worlds.